Determining the Effect of Galectin Insertion on Membrane Organization - Browne, Danielle; Weissbarth, Yvonne (URJ-UCCS: Undergraduate Research Journal at UCCS, 2020)
Interactions between Galectin proteins and GM1 glycolipids are largely unspecified, but studies have shown that interactions between the two molecules exhibit biorelevant cellular responses by signaling pathways, regulating inflammatory response and tumor growth. Experiments using a model membrane’s surface pressure, mean molecular area, fluorescence microscopy, and GIXD/Reflectivity X-ray analysis has identified model membrane rearrangements in vitro at biologically relevant concentrations. Gal-1WT was tested using Langmuir Trough experiments and induced a surface pressure increase at a constant mean molecular area with model membrane 95:5 DPPC:GM1 in 8:2 chloroform and methanol. X-ray data was collected for Gal-1WT using 95:5 DPPC:GM1 model cellular membrane in a Langmuir trough. Fluorescent microscopy was used to observe an increased presence of lipid dense domains within the membrane. Analysis using the collected Grazing Incidence X-ray Diffraction and X-Ray Reflectivity determines the location of Galectin interaction with the membrane as well as the change in membrane organization over the duration of the experiment. Further data analysis will be done on mutants: Gal-1 [GG] Gal-1, Gal-1 [8S] Gal-1, Gal-3NT/1, Gal-1 [GG], Gal-3, trGal-3, and Gal-3_Gal-3. Analysis of mutants will allow for further description of specific quaternary structure influences on membrane organization.